DEVELOPMENT OF A SPACE-EFFICIENT AND LIGHTWEIGHT STUDY TABLE FOR ISLAMIC BOARDING SCHOOL STUDENTS - Raharjo, Wijang Wisnu; Diharjo, Kuncoro; Ariawan, Dody; Raharjo, Wahyu Purwo; Kusharjanta, Bambang; Triyono (Abdi Masya, 2025)
This study presents the design, fabrication, and evaluation of a space-efficient, lightweight, and foldable study table intended to enhance learning conditions in Islamic boarding school (pesantren) environments. The table was designed using Computer-Aided Design (CAD) software with a focus on ergonomic principles, particularly a recommended working height of 70 cm to support proper posture. The final product features a durable steel tube frame, a plywood tabletop, and a collapsible leg mechanism, enabling compact storage in limited dormitory spaces. The fabrication process included precision cutting, Shielded Metal Arc Welding (SMAW), and the application of rust-resistant enamel paint, resulting in a total weight of approximately 6.5 kg with a load capacity of 40 kg.To evaluate its effectiveness, five students participated in comparative study sessions using both the old and the new table under controlled conditions. Concentration duration, used as the primary performance indicator, increased from an average of 264 seconds with the old table to 359 seconds with the new one—an improvement of 95 seconds or 36.43%. This enhancement is attributed to improved ergonomic posture, structural stability, and positive psychological effects stemming from user involvement and aesthetic design. The foldable design also allows better space utilization in multifunctional boarding school rooms. Overall, the table demonstrates significant functional and educational benefits and offers a scalable, low-cost solution for learning environments in resource-constrained settings. Future improvements may include using lighter materials and integrating storage or seating features to further improve user experience and usability.